Bulldozed and Betrayed : Louisiana and the Stolen Elections of 1876 - Fairclough, Adam (Book collections on Project MUSE., 2021)
"In 1878 and 1879, the Potter Committee, created by the Democrat-controlled House of Representatives, conducted an extensive investigation into the disputed presidential election of 1876 that pitted Rutherford B. Hayes against Samuel J. Tilden. It aimed to discredit President Hayes's title to the presidency by showing that the Republican party had carried the vital states of Florida and Louisiana by fraud. The committee alleged that nationally prominent Republicans, sent to those states by President Grant to observe the count, had encouraged local officials to make spurious charges that Democrats had carried the election by intimidating Black voters. These false charges of Democratic 'bulldozing' had furnished a pretext for returning boards to reject enough Democratic votes to hand victory to Hayes. The investigation focused on the actions of Senator John Sherman, who supposedly promised federal jobs to two local election supervisors if the latter stood by their false claims of Democratic intimidation. Sherman made the promise in a letter, committing what was tantamount to a bribe in the process, Democrats charged. Although several historians have studied the disputed election of 1876, Adam Fairclough is the first to offer a comprehensive analysis of the Potter Committee's investigation. The inquiry, Fairclough shows, was quite revealing about the character of politics at that time. The committee failed to authenticate the 'Sherman letter,' which was likely a fake. It also failed to establish that Republican charges of Democratic intimidation were false. Its key witnesses were disgruntled Republicans who perjured themselves. Other important witnesses later withdrew their testimony and charged Democrats with intimidation and bribery. The investigation took an unexpected turn that added to the Democrats' embarrassment when the New York Tribune translated and published dozens of coded telegrams passed between the Tilden headquarters in New York and Democratic agents in the disputed southern states during the election. The 'cipher dispatches' showed that the Tilden campaign had attempted to buy the presidency by bribing election officials and presidential electors. This development neutralized the use of the fraud issue by the Democratic party. It also ended Tilden's political career. As Fairclough deftly shows, the committee hearings were compelling, sensational, and sometimes hilarious. As he also reveals, testimony from witnesses provides keen insight into the political culture of the time by illustrating the dishonesty and venality of many southern Republicans. It demonstrates, too, the pervasive influence of the 'spoils system,' whereby political loyalties were often determined by whether one had a government position, and, if so, to whom one owed the appointment. Moreover, thanks to aggressive questioning by the maverick Republican Ben Butler, the investigation exposed the treachery of Hayes and his inner circle. They took the electoral votes of Louisiana and South Carolina and then permitted insurrectionary Democrats to overthrow Republican governments in those states-governments elected with the same votes that elected Hayes. In the South, the tragic aftermath of the so-called Compromise of 1877 was further intimidation of Black voters, the murder of more Republican leaders, and longtime Democratic rule"--